Night-to-night sleep variability in adolescent rugby players compared to non-athlete matched controls - Saidi, O.; Del Sordo, G.; Peyrel, P.; Sudlow, A.; Maso, F.; Walrand, S.; Duché, P. (International Journal of Sports Science & Coaching, 2023)
Despite the importance of sleep monitoring in the context of sport, few studies to date examined night-to-night sleep variability among adolescent athletes. This study compared night-to-night sleep variation between junior rugby players and age-matched non-athlete adolescents across seven consecutive nights of the in-season competitive phase. This investigation is based on data from a single centre, observational prospective study including 30 adolescents (15 junior rugby players and 15 non-athlete age-matched controls). Sleep was continuously monitored using ambulatory electroencephalogram (EEG) recordings. While the non-athlete controls catch-up on their sleep debt during the weekend by delaying their wake-up time, junior rugby players opt for an earlier bedtime to cope with sport-related travel (Fri: -00:57 h:min; p < 0.001; Sat: -01:58 h:min; p < 0.001) or early school (Mon: -00:55 h:min; p < 0.001). Night-to-night sleep examination identified greater sleep disturbances in junior rugby players the nights before and after the competition SE (Fri: -11%; p < 0.001; Sat: -9 min; p < 0.01). Junior rugby players showed higher IIV in sleep duration (CVTST: + 5.8%; P < 0.001), efficiency (CVSE: + 3.8%; p < 0.001) and staging (CVN2: + 5.4%; p < 0.001; CVN3: + 4.5; p < 0.01 IIV; REM: + 16.4%; p < 0.01). Higher IIV in the young athletes` sleep outcomes could make them even more vulnerable to health and wellness concerns (i.e. overtraining, injury). The study results show the urgent need for an appropriate consideration of sleep regularity in young athletes.